PROPOSAL FOR A HOLISTIC MINDFULNESS-BASED INTERVENTION PROGRAM FOR THE CLASSROOM TEACHERS WITH MENTAL HEALTH PROBLEMS - Nguyen Phuong Lan; Huynh Cong Du (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In the school setting, the mental health problems of students have been often discussed. Teachers have also been found to have the mental health problems, which could have a detrimental effect upon all of those students who are associated with him or her, but there has been no or very few interventions designed to help them. To address this, the current study has two main goals: 1) to review related literature in order to categorize common mental health problems among teachers and 2) to propose a holistic mindfulness-based intervention program for the teachers. The proposed program consists of 2 modules with 9 sessions. Each session is expected to last in 60 minutes.